Experiential Science Learning Practices and Learner Engagement in Multigrade Classrooms: Insights from Dibewan Integrated School, Palanan, Isabela: Experiential Science Learning Practices and Learner Engagement in Multigrade Classrooms: Insights from Dibewan Integrated School, Palanan, Isabela - ALMONTE, DIANA (Studies in Technology and Education, 2026)
Abstract Experiential learning practices play a vital role in strengthening learner engagement and meaningful understanding in science education, particularly within multigrade classroom settings. This study explored experiential science learning practices and learner engagement in multigrade classrooms at Dibewan Integrated School, Palanan, Isabela. Anchored on Experiential Learning Theory and Constructivist Learning Theory, the study employed a descriptive qualitative research design to examine instructional practices, classroom participation, learner experiences, and engagement in science learning activities. Participants included multigrade learners and science teachers of Dibewan Integrated School. Data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Braun and Clarke’s (2006) thematic analysis approach was utilized in analyzing the gathered data. Findings revealed that hands-on activities, collaborative learning, contextualized science instruction, outdoor exploration, and practical experimentation significantly strengthen learner participation and engagement in multigrade science classrooms. Learners demonstrated greater curiosity, motivation, and conceptual understanding when science lessons were connected to environmental experiences, local resources, and real-life applications. The findings further revealed that supportive teacher facilitation and learner-centered instructional practices contribute significantly to behavioral, emotional, and cognitive engagement in science learning. However, challenges such as limited instructional resources, time management difficulties, varying learner abilities, and classroom management concerns affected instructional implementation and learner participation. The study concludes that experiential and contextualized science learning practices significantly contribute to meaningful engagement and scientific understanding among multigrade learners. Strengthening localized science instruction, collaborative learning strategies, and experiential teaching approaches is recommended to improve learner participation and engagement in multigrade science education. Keywords: experiential learning, science education, learner engagement, multigrade classrooms, contextualized instruction, qualitative research, science learning practices